Molecole d'autore in cerca di memoria Dramma scientifico-civile in due atti - Dei, Luigi (Libere carte, 2020)
Freely adapted from Primo Levi's The Periodic Table, the drama takes place in a Fahrenheit 451-like scenario. In this world without books or memory, a man from the street appears with some pieces of paper, almost undecipherable: with the help of the narrative voice, of his friends - Science, Technology and Nature - and of two actors, Primo and his friend Alberto, the man manages to reconstruct the episode Cerium's story. Thanks to the memory, the lost identity, that is our story, is reconstructed. Science, Technology and Nature allow the man without memory to take possession of scientific knowledge and to emancipate himself from his state. The drama finds its catharsis by taking a moving turn, inspired by the short story Carbon, which lyrically creates a timeless connection between a carbon atom of the smoke of a crematorium and the same atom dwelling in the body of some of us, a poetic parable of a science immersed in the life and history of man.